2014
DOI: 10.12968/bjom.2014.22.7.495
|View full text |Cite
|
Sign up to set email alerts
|

Exploring same sex couples' experiences of maternity care

Abstract: Same sex parenthood is becoming increasingly prevalent around the world. More same sex couples are engaging with maternity services, and as a ‘vulnerable’ group in health care it is imperative that their needs are met ( Burkholder and Burbank, 2012 ). This literature review explores research from around the world to evaluate the care that same-sex parents receive in the maternity sector. No articles were found to include gay men; however, 13 articles focused on lesbian parents. Three main themes arose from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Numerous studies also find that pregnant sexual minority women experience prejudice and homophobia from health care providers and medical staff during pregnancy and childbirth, including disparaging comments, lack of respect, and heteronormative language insensitive to the needs of diverse families (e.g., assuming the co-parent is a father rather than a mother) (Dahl, Margrethe Fylkesnes, Sørlie, & Malterud, 2013;Hammond, 2014;Harvey, Carr, & Bernheine, 1989;Larsson & Dykes, 2009;Lee, Taylor, & Raitt, 2011). Sexual minority women also report being worried about societal-based discrimination and stigma harming their families (Gartrell et al, 1996).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Numerous studies also find that pregnant sexual minority women experience prejudice and homophobia from health care providers and medical staff during pregnancy and childbirth, including disparaging comments, lack of respect, and heteronormative language insensitive to the needs of diverse families (e.g., assuming the co-parent is a father rather than a mother) (Dahl, Margrethe Fylkesnes, Sørlie, & Malterud, 2013;Hammond, 2014;Harvey, Carr, & Bernheine, 1989;Larsson & Dykes, 2009;Lee, Taylor, & Raitt, 2011). Sexual minority women also report being worried about societal-based discrimination and stigma harming their families (Gartrell et al, 1996).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Three literature reviews showed that same‐sex mothers experienced heteronormativity, prejudices, overt and covert discrimination and homophobia, insufficient acknowledgement and support. RHPs lacked knowledge about LGBTQ, but also showed positive attitudes towards the same‐sex mothers . Treating the non‐birthing mother as an equal parent was important for a positive experience.…”
Section: Introductionmentioning
confidence: 99%
“…, Dahl et al . , Hammond ). However, the health of a community is affected by the amount and types of support it receives.…”
Section: Introductionmentioning
confidence: 99%
“…), literature reviews have focused more on lesbian mothers (Dahl et al . , Hammond ); referred to in this study as same‐sex mothers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation